A Matter of Scale - Wang‐Ping Chen (Perspectives of Earth and Space Scientists)
Abstract Plate tectonics, one of the greatest scientific discoveries of the twentieth century, works particularly well in oceanic regions but has considerable difficulty to account for widespread, diffuse deformation of the continents. There has been an enduring discourse on whether continuous deformation of the crust or slip along discrete faults is a better approximation of continental tectonics. A key difficulty in resolving this issue is that the distinction between flow and slip is scale dependent. Moreover, even at scales of tens of millimeters or less, both mechanisms of deformation can coexist. Over times much longer than about 100 years, the limit of reliable geophysical data, the scale in time further complicates the problem of spatial scales. However, solutions to some problems in continental tectonics do not rely on end‐member models, and advances in understanding the role of the lithospheric mantle beneath the continental crust point the need to extend our focus below the crust.